SENAM AEROBIK DAN KECEMASAN MAHASISWA ASAL DAERAH TERTINGGAL, PERBATASAN, DAN KEPULAUAN - Herawati, Lucky; Maryana; Suhardjono (Universitas Jenderal Achmad Yani Yogyakarta, 2015)
Background: Student anxiety is estimated as a cause of low students' academic achievement of colaborated clas from remote areas, border and island with Poltekkes Kemenkes Yogyakarta. Objective: The purpose of this studi was to determine the effect of student participation in gymnastics earobik to decrease student anxiety. Method: The treatment such as student participation in aerobic Pre-experimental research, pre-posttest was conducted 39 respondents, taken from department of Dental Nursing Diploma. The treatment such as student participation in aerobics, held in July 2014 at the campus Department of Dental Nursing, Jalan Kyaimaja Yogyakarta. The research results were measured the decrease of anxiety, using the State Trait Anxiety Inventory questionnaire. Results were analyzed using a one sample T-test, 95% Confidence Intervals. Result: Research results obtained that there was significantly decreased anxiety after students do aerobics every morning for 1 month (p value = 0.000). Decreased anxiety occurs at 21.21%. Decrease anxiety in female students is higher than the decrease in anxiety male students. Conclution: The studi Conclude that participation in aerobic activity can reduce anxiety in students from remote areas, borders, and islands. Key wors: Aerobic, anxiety, students from remote areas